The impact of pre-school student achievement in: a case study - Ronaldo CÃlio Pereira (2012)
Considered as priority, especially, in the beginning of the life, the prÃ-school has great weight in the individual's educational and social formation when he frequents the school earlier. The literacy integrates a democratic dimension of the function of the school. This because the socialization of the writing, interferes in the widest problem of the school failure, lived by a great contingent of students originating from of the popular layers, that frequent the Brazilian public schools. The literary revision that treats of the contribution of the study and of researches that appear for the importance of inserting the child earlier, he/she is a consent in that many educators believe to be that very important attitude for the development social, cognitive and of easier and useful learning for the child. With the objective of evaluating the importance of the pre-school in the child's development cognitive, educational and social before arriving the initial series at the school, where that learning can help her/it to learn with more easiness and larger agility, once he/she brings with itself a load of acquired knowledge in the pre-school. The methodology used in the elaboration of that work it was based in studies of bibliographical character in books, goods and works that treat of the theme, whose larger purpose is of emphasizing the importance of inserting the child in the pre-school as part of your learning.